A new approach to solve complex valued systems arising from the solution of Maxwell equations in the frequency domain through real‐equivalent formulations. Issue 2 (21st December 2016) - Marioni, L.; R. Alves Z., J.; Hachem, E.; Bay, F.
Summary: The purpose of this article is to propose algebraic techniques to solve symmetric complex‐valued systems. In particular, we focus on the systems which arise from the modeling of electromagnetic fields in the frequency domain. These systems usually present a very ill‐conditioned number, so specific preconditioning techniques are supposed to be used. Finally, both analytical and numerical reference tests are proposed on the simple case of the magnetic field produced by a solenoid containing conductive or non‐conducting materials.